The apicomplexan parasite Toxoplasma gondii - Delgado, Inês (2022)
Toxoplasma gondii is a ubiquitous zoonotic parasite with an obligatory intracellular lifestyle. It relies on a specialized set of cytoskeletal and secretory organelles for host cell invasion. When infecting its felid definitive host, T. gondii undergoes sexual reproduction in the intestinal epithelium, producing oocysts that are excreted with the feces and sporulate in the environment. In other hosts and/or tissues, T. gondii multiplies by asexual reproduction. Rapidly dividing tachyzoites expand through multiple tissues, particularly nervous and muscular tissues, and eventually convert to slowly dividing bradyzoites which produce tissue cysts, structures that evade the immune system and remain infective within the host. Infection normally occurs through ingestion of sporulated oocysts or tissue cysts. While T. gondii is able to infect virtually all warm-blooded animals, most infections in humans are asymptomatic, with clinical disease occurring most often in immunocompromised hosts or fetuses carried by seronegative mothers that are infected during pregnancy.